Evaluation of a Community Social Responsibility (CSR) Program Based on a Community Satisfaction Index: A Case Study of the Kasih Bumi and Ruang Tumbuh Kalisogo Programs at PT Perusahaan Gas Negara OMM Region III - Purwanto, Wahyu; Nur Mashitohiyah; Faiz Salman Ar-rosyid (Prospect Publishing, 2025)
Abstract This study aims to measure and analyze the level of Community Satisfaction Index (CSI) among beneficiaries of the Corporate Social Responsibility (CSR) programs—KASIH BUMI and Ruang Tumbuh Kalisogo—organized by PT Perusahaan Gas Negara (PGN) OMM Region III in Sidoarjo Regency, East Java. The method employed is census (saturated sampling), with the CSI calculated using the weighted average value formula. The overall CSI result showed a value of 3.78 (Converted Value: 94.5), which places the program's performance in the